ARTIFICIAL INTELLIGENCE IMPACT ON LEGAL, EDUCATION AND GENERAL RIGHTS OF CHILDREN - Akhtar, Rehman (Journal of Peace, Development and Communication, 2023)
The science of Artificial Intelligence (AI) has a wide range of methodologies, breakthroughs in machine learning, deep learning, and encourages a paradigm change in almost all areas of the IT sector. AI is utilised in towns for traffic management and safety of the people; in the infirmaries, through applications in equipment that help doctors diagnose diseases; through the application of algorithms in education, which allow for individualised learning. The emergence of AI is a global phenomenon linked to what is frequently referred to as the 4th Industrial Revolution. Children are also impacted by the increasing integration of artificial intelligence-based technologies into modern life. The possible influence of AI on children warrants special consideration. We already know that artificial intelligence will affect practically every part of our life, despite the fact that there are still many unsolved questions about it. However, children will be more affected in many ways due to factors such as how they are born, the resources and learning techniques that are available to them, as well as the jobs that they will be trained for. This truth carries enormous opportunities and peril. The issue is that when AI hurts children, the harm will follow them into adulthood and last for a very long period. However, AI for kids has enormous potential for enhancing learning, development, safety, and opportunity. All of these conversations must start right away since children’s healthy development is essential to the future prosperity of every country, and disappointing our children’s generation would be extremely costly. The purpose of the current article is to examine how AI may, indirectly or directly, affect the lives of children and their educational processes.